The Influence of Tiktok Shop on Skincare Purchasing Decisions Among Female Students - Yani, Annisa dina maisarah; Nandita Olivia Natasya; Ananda Fazhira (Outline Journal of Management and Accounting, 2026)
This study aims to analyze the influence of TikTok Shop on skincare purchasing decisions among female students. Rapid digital development has changed people's shopping patterns, marked by the emergence of social commerce trends such as TikTok Shop. Female students are a highly active consumer group following skincare trends, and TikTok Shop makes it easy for them to purchase products spontaneously simply by watching short videos or live streaming. he research method used was descriptive qualitative, with a questionnaire distributed to 30 female students in the Economics Education Study Program, class A, who actively use and have shopped at TikTok Shop (purposive sampling). This questionnaire was designed to explore the dominant factors influencing impulse buying decisions. The results showed that TikTok Shop significantly influenced female students' skincare purchasing decisions, with 75.7% of respondents agreeing/strongly agreeing. The primary driving factors were social proof and trust. The power of product reviews was the highest (87.9% agreed/strongly agreed), followed by influencer influence (81.9%) and friend recommendations (81.8%). These findings indicate that trust, built through credible figures and reviews, is key in triggering quick and spontaneous purchases.